Pengetahuan dan kepatuhan tenaga kesehatan menggunakan alat pelindung diri saat merawat pasien Coronavirus diseases (Covid-19): Sebuah tinjauan literatur - Devi Nugrehaini; Suyanto Suyanto (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: MERS CoV and Covid-19 is a new type of infectious disease that has never been previously identified in humans and can be transmitted from human to human through droplets that come out when coughing or sneezing. Health workers who treat Corona Virus patients must protect their condition against transmission by using personal protective equipment. For this reason, it is necessary to study knowledge and compliance with the use of personal protective equipment for health workers so that services can be provided better.Purpose:This study aims to analyze the relationship between knowledge and adherence to the use of personal protective equipment (PPE) in health workers during treat patient with Corona Virus.Method: This study is a literature review study that focuses on research articles on knowledge, compliance and personal protective equipment. Through a search using several literature data bases such as PubMed, Google Scholar, Crossreff and Wiley, 353 articles were obtained. After going through the screening using the inclusion and exclusion criteria in PICOT, 10 articles were selected.Results. The analysis of selected articles shows that the knowledge of health workers about personal protective equipment for health workers is quite good but compliance with using it is still low.Conclusion: There is a relationship between knowledge and compliance with the use of PPE. Compliance can be increased by increasing knowledge and access to PPE and ease of use supported by workplace institutionsKeywords: Compliance; Personal Protective Equipment; MERS COV; Covid 19Pendahuluan: MERS CoV dan Covid-19 adalah penyakit menular jenis baru yang belum pernah diidentifikasi sebelumnya pada manusia dan dapat ditularkan dari manusia ke manusia melalui droplet yang keluar saat batuk atau bersin. Tenaga kesehatan yang menangani Corona Virus kondisinya harus dijaga terhadap penularan dengan penggunaan alat pelindung diri. Untuk itu perlu dikaji pengetahuan dan kepatuhan penggunaan alat pelindung diri petugas kesehatan agar pelayanan dapat diberikan lebih baik. Tujuan: Penelitian ini bertujuan menganalisis hubungan antara pengetahuan dan kepatuhan penggunaan alat pelindung diri (APD) pada tenaga kesehatan selama merawat pasien yang menderita Corona Virus .Metode: Penelitian ini berupa studi literatur review yang fokus pada artikel penelitian tentang pengetahuan, kepatuhan dan alat pelindung diri. Melalui penelusuran menggunakan beberapa data base literature seperti PubMed, Google Scholar, Crossreff dan Wiley diperoleh 353 artikel. Setelah melalui penyaringan menggunakan kriteria inklusi dan eksklusi dalam PICOT diperoleh 10 artikel terpilihi. Hasil. Analisa artikel terpilih menunjukkan bahwa pengetahuan tenaga kesehatan tentang alat pelindung diri tenaga kesehatan cukup baik namun kepatuhan menggunakannya masih rendah. Simpulan: Ada hubungan antara pengatahuan dan kepatuhan penggunaan APD. Kepatuhan dapat meningkat dengan peningkatan pengetahuan dan akses APD serta kemudahaan dalam penggunaannya yang didukungan oleh institusi tempat kerja